State politics and panchayats in India - "Ghosh, Buddhadeb" (New Delhi, 2003)
This book tries to look into the linkages between the panchayats and state level politics. This, in turn, has enabled them to identify the political factors that have so far determined the course of decentralization in India. Their findings are based on the case studies of four states, namely, Maharashtra, Gujarat, West Bengal and Bihar.
Keywords: Panchayats-India